Hospice utilization of Medicare beneficiaries in Hawai'i compared to other states - Deborah Taira; Merle Kataoka-Yahiro; Angela Sy (JMIR Publications, 2017)
The objective is to examine hospice utilization among Medicare beneficiaries in Hawai'i compared to other states. Data were from the 2014 Medicare Hospice Utilization and Payment Public Use File, which included information on 4,025 hospice providers, more than 1.3 million hospice beneficiaries, and over $15 billion in Medicare payments. Multivariable linear regression models were estimated to compare hospice utilization in Hawai'i to that of other states. Control variables included age, gender, and type of Medicare coverage. Medicare beneficiaries using hospice in Hawai'i differed significantly from beneficiaries in other states in several ways. Hawai'i beneficiaries were more likely to be Asian (57% vs. 1%, p < .001) and "other race" (10% vs. 0.1%, p < .001), and less likely to be White (28% vs. 84%, p < .001). Hawai'i beneficiaries were also more likely to have Medicare Advantage (55% vs. 30%, p = .05). Regarding primary diagnoses, hospice users in Hawai'i were significantly more likely to have a primary diagnosis of stroke (11% vs. 8%, p = .03) and less likely to have respiratory disease (5% vs. 11%, p = .003). In addition, hospice users in Hawai'i were more likely to use services in their homes (74% vs. 52%, p = .03). Hawai'i hospice users were also less likely to die while in hospice (42% vs. 47%, p = .002). Characteristics of Medicare beneficiaries in Hawai'i differ from those in other states, regarding demographic characteristics, type of coverage, primary diagnoses, likelihood of using services in their homes, and death rates. Further research is needed to better understand factors affecting these differences and whether these differences warrant changes in policy or practice.